2020
DOI: 10.1017/s1368980020004826
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary patterns and risk of breast cancer in Chinese female population: a latent class analysis

Abstract: Objective: To determine if specific dietary patterns are associated with breast cancer risk in Chinese women. Design: Latent class analysis (LCA) was performed to identify generic dietary patterns based on daily food-frequency data. Setting: The Chinese Wuxi Exposure and Breast Cancer Study (2013-2014). Participants: A population-based case-control study (695 cases, 804 controls). Results: Four dietary patterns were identified, Pruden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The dietary patterns derived from LCA were described in our previous studies ( 33 ). As described briefly below, latent class models were fitted for two to six classes, and the four classes were chosen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dietary patterns derived from LCA were described in our previous studies ( 33 ). As described briefly below, latent class models were fitted for two to six classes, and the four classes were chosen.…”
Section: Resultsmentioning
confidence: 99%
“…What deserves attention is the Picky -class, which is similar to the “ Salty -pattern” in a previous study ( 53 ), women in the Picky -class were characterized by higher extreme probabilities of non-consumption on specific foods, the highest probabilities in consumption of pickled foods, and the lowest probabilities in consumption of cereals, soy foods, and nuts. The risk of the Picky -class may come from an imbalance diet that could lead to the loss of certain vital nutrients and a high consumption of pickled foods that are prone to inflammation ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diet acknowledgedly p lays an important role in the development of insulin resistance, in particular glucose serum levels 29 , 30 , and the potential contributions of diet to body composition, inflammation, VAI, and TyG index have also been reported 11 , 21 , 31 , 32 . A study among medical university students in China that examined the impact of different dietary pattern on body composition showed that the Western pattern influenced FMI/FFMI ratio positively, while the "vegetable and fruit" pattern influenced FMI/FFMI ratio negatively 33 .…”
Section: Discussionmentioning
confidence: 99%